A fast extension for sparse representation on robust face recognition - Qiu, Hui-ning; Pham, DucSon; Venkatesh, Svetha; Liu, Wan-quan; lai, Jian-huang (Springer, 2010)
We extend a recent Sparse Representation-based Classification (SRC) algorithm for face recognition to work on 2D images directly, aiming to reduce the computational complexity whilst still maintaining performance. Our contributions include: (1) a new 2D extension of SRC algorithm; (2) an incremental computing procedure which can reduce the eigen decomposition expense of each 2D-SRC for sequential input data; and (3) extensive numerical studies to validate the proposed methods.